Griseofulvin, diketopiperazines and cytochalasins from endophytic fungi colletotrichum crassipes and Xylaria sp., and their antifungal, antioxidant and anticholinesterase activities - Chapla, Vanessa M. [UNESP] (2018)
One new natural product, 1-phenylethyl-O-α-L-rhamnopyranoside, together with eight known diketopiperazines and two benzene derivatives were isolated from the endophytic fungus Colletotrichum crassipes, whereas six known compounds including two griseofulvins, three cytochalasins and one dihydroisocoumarin were produced from the endophyte Xylaria sp., both endophytic fungi are associated with leaves of Casearia sylvestris. Cyclo(D)-Pro-(D)-Phe, N-(2-phenylethyl)acetamide and 5-carboxy-6-hydroxy-3-methyl-3,4-dihydroisocoumarin exhibited potent antifungal activity against Cladosporium cladosporioides and C. sphaerospermum. The compounds cyclo(D)-Pro-(D)-Phe, griseofulvin, cytochalasin B and cytochalasin D exhibited antioxidant activity, and the compounds cyclo(D)-Pro-(D)-Phe, cytochalasin B and cytochalasin C showed potent acetylcholinesterase (AChE) inhibition. In addition, this is the first report on the isolation of secondary metabolites from two endophytic fungal strains, associated with Casearia sylvestris. Printed in Brazil-